Environmentally benign synthesis of substituted iodinated flavones as precursors for prenyl-/geranyl flavones from the corresponding chalcones - Khan, Sumaiya; Liza, Umme Aiman; Banik, Dipan; Aman, Md Aman Ullah; Happy , Kamrunnahar; Arjaya, Amit Chandra; Hossain, Mohammad Mamun (European Journal of Chemistry, 2024)
Flavones have biological properties because of the existence of oxoheterocyclic ring moieties, and day by day create research interest areas because of their important biological activity. Iodine-substituted flavones were synthesized from the corresponding chalcones through an exhaustive iodination reaction. Generally, it is seen that halogenated flavones show better biological activity. Moreover, the introduction of iodine in the ring moiety facilitates the incorporation of highly active side chains, such as prenyl and geranyl groups through the formation of C-C bonds by numerous coupling reactions such as Sonogashira coupling. To achieve such target molecules, a planned chemical synthesis was conducted. For comparison, microwave irradiation (MWI) and conventional heating (CH) methods were used to synthesize a series of iodine-substituted flavone compounds with different substitutes (4a-d) from their corresponding chalcones (3a-d). Unfortunately, 3e chalcone (1-hydroxynapthalene substituted flavone) did not convert to 4e flavones. In the microwave method, a notable decrease in time required in the reaction and an increase in % yield of the reaction were remarked. Characterization and conformation of all synthesized compounds were done using ultraviolet, infrared, and nuclear magnetic resonance spectroscopy and elemental analysis.